Investigation of Hull Design Modifications on Fuel Consumption and Energy Efficiency Design Index (EEDI) - Betty Ariani; Rizky Chandra Ariesta; Rembo Prasetya; Marista Oktaviani; Mohammad Hanifuddin Hakim (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2022)
Currently, efforts are focused on reducing emissions to support carbon neutrality by 2050 through green technology. Green technology applies to the ship's design, port, engine selection, fuel, and operation. This study modified the hull to reduce drag and improve fuel efficiency. Changes were made based on variations in the deadrise angle, which were analyzed using numerical simulation. In the current situation, the deadrise angle is changed from 9° to 10°, 15°, and 20°. On the angle variation, the effects of changes in ship drag, fuel, and energy efficiency design index were analyzed (EEDI). The method simulates computational fluid dynamics with a Holtrop calculation method validation approach. At 12 and 6 knots above the current deadrise, resistance is reduced by 8.2% and 6.8%, respectively. The fuel efficiency achieved is 6.9% at 6 knots and 8.2% at 12 knots, resulting in monthly fuel savings of 2.43 tonnes. Furthermore, the phenomenon of the EEDI value at the lowest resistance and highest speed has a decreased performance value. Reducing the speed from 12 to 9 knots improves the performance of EEDI by 66%